Evidence of a disability paradox in patient‐reported outcomes in haemophilia. Issue 2 (17th February 2021) - O'Hara, Jamie; Martin, Antony P.; Nugent, Diane; Witkop, Michelle; Buckner, Tyler W.; Skinner, Mark W.; O'Mahony, Brian; Mulhern, Brendan; Morgan, George; Li, Nanxin; Sawyer, Eileen K.
Abstract: Introduction: People with inherited and long‐term conditions such as haemophilia have been shown to adapt to their levels of disability, often reporting better quality of life (QoL) than expected from the general population (the disability paradox). Aim: To investigate the disability paradox in people with haemophilia in the United States by examining preference differences in health state valuations versus the general population. Methods: We conducted a discrete choice experiment including duration to capture valuations of health states based on patient‐reported preferences. Participants indicated their preferences for hypothetical health states using the EQ‐5D‐5L, where each participant completed 15 of the 120 choice tasks. Response inconsistencies were evaluated with dominated and repeated scenarios. Conditional‐logit regressions with random sampling of the general population responses were used to match the sample of patients with haemophilia. We compared model estimates and derived preferences associated with EQ‐5D‐5L health states. Results: After removing respondents with response inconsistencies, 1327/2138 (62%) participants remained (177/283 haemophilia; 1150/1900 general population). Patients with haemophilia indicated higher preference value for 99% of EQ‐5D‐5L health states compared to the general population (when matched on age and gender). The mean health state valuation difference of 0.17 indicated a meaningful difference compared to a minimal clinically important difference threshold of 0.07. Results were consistent by haemophilia type and severity. Conclusion: Our findings indicated the presence of a disability paradox among patients with haemophilia, who reported higher health states than the general population, suggesting the impact of haemophilia may be underestimated if general population value sets are used.